ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP PERSEDIAAN BAHAN HABIS PAKAI LPP TVRI SUMATERA UTARA - Putri, Ranti Gatrizka; Zulkarnen, Zuliana; Chrisna, Heriyati (UNIVERSITAS DHARMAWANGSA, 2023)
here are still many companies especially in service companies that do not have a special system for thesupply of used materials. The study aims to provide an overview of the application of accountinginformation systems to the inventory of used materials and look at the effectiveness of such systems. Theobject of this research is carried out in the LPP TVRI North Sumatra Type and source of data obtainedin this research are primary data and secondary data. Based on the research data obtained, the authorsused data collection methods by means of interviews, documentation, and library surveys. The results ofthis study showed that the LPP TVRI Sumatera Nord uses a computerized recording system, i.e. everytransaction, both inputs, outputs and returns of goods will be directly input into the existing system on acomputer based database. The advantage in using this system is that the collection of information canbe done quickly and easily, can perform data protection and security, while the shortcomings in the useof this system, i.e. the system used by LPP TVRI Sumatera North must be updated in accordance withthe provisions of the Ministry of Finance of the Directorate General of the Treasury RI so that it willprevent the continuation of recording activity for a few moments until the database is completed to berenewed, when there is an inaccurate access damage can occur and a more skilled user is required inprocessing data.